EARLY DIAGNOSIS OF RENAL DYSFUNCTION IN HIGH-RISK PATIENTS WITH ISCHEMIC HEART DISEASE - Rakhimova M.E; Norbo‘toyev O.M; Mirzayev O.V.; Abdullayeva O.Y. (Scholar Express Journals, 2024)
Early diagnosis of changes in kidney function in patients with coronary heart disease (CHD), taking into account existing risk factors (RF) and comorbid conditions, has not been sufficiently studied and is currently considered one of the urgent problems of medicine. This article represents the results of investigation dedicated to the renal dysfunction in patients with stable angina. The results obtained and their analysis confirmed that the calculation of GFR based on serum cystatin C, the determination of fetuin A in the blood, proteinuria and podocyturia allows early diagnosis of renal dysfunction (RD) in CKD
Keywords: atherosclerosis; risk factor; impaired renal function; coronary heart disease